Hess: Tocqueville and Beaumont - Lyon, E. Stina (Serendipities. Journal for the Sociology and History of the Social Sciences, 2018)
Book review of: Hess, Andreas. 2018. Tocqueville and Beaumont: Aristocratic Liberalism in Democratic Times. Cham, Switzerland: Palgrave Macmillan. First Hardback ed., v + 153 pp. ISBN 978-3-319-69666-9 Price: € 51,99